Pro spring batch - Minella, Michael T. (Berkeley, California Apress, 2011)
Since its release, Spring Framework has transformed virtually every aspect of Java development including web applications, security, aspect-oriented programming, persistence, and messaging. Spring Batch, one of its newer additions, now brings the same familiar Spring idioms to batch processing. Spring Batch addresses the needs of any batch process, from the complex calculations performed in the biggest financial institutions to simple data migrations that occur with many software development projects. Pro Spring Batch is intended to answer three questions:   What? What is batch processing? What does it entail? What makes it different from the other applications we are developing? What are the challenges inherent in the development of a batch process? Why? Why do batch processing? Why can't we just process things as we get them? Why do we do batch processing differently than the web applications that we currently work on? How? How to implement a robust, scalable, distributed batch processing system using open-source frameworks Pro Spring Batch gives concrete examples of how each piece of functionality is used and why it would be used in a real-world application. This includes providing tips that the "school of hard knocks" has taught author Michael Minella during his experience with Spring Batch. Pro Spring Batch includes examples of I/O options that are not mentioned in the official user's guide, as well as performance tips on things like how to limit the impact of maintaining the state of your jobs. The author also walks you through, from end to end, the design and implementation of a batch process based upon a theoretical real-world example. This includes basic project setup, implementation, testing, tuning and scaling for large volumes.
Electronic reproduction.
Keywords: Electronic data processing -- Batch processing; Java (Computer program language)